2015
DOI: 10.3390/wevj7030475
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Evaluation of a Plug-in Hybrid Vehicle under European Procedure, Worldwide Harmonized Procedure and Actual Use

Abstract: This paper describes a two-fold approach carried out in collaboration between IFPEN and the French ADEME with the aim to evaluate a Plug-in Hybrid vehicle according to its conditions of use. The vehicle considered, an Opel Ampera, has been widely tested on a chassis dyno and simulated using IFPEN LMS.IMAGINE.Lab AMESim® platform. The software principles and its validation on different specific cases, thanks to experimental results, are described. The PHEV simulation tool is used to evaluate the influence of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…They suggested that the main factors explaining this variation are the annual mileage, the regularity of daily driving, and the likelihood of long-distance trips. As Badin et al recently reported, higher emission factor would be expected if U.S. UFs are used in our study. As reported in WLTP regulation, once a significant number of PHEVs will be on the market, UF factors will have to be modified to be able to better capture their real usage and coherently assign the correct weighting to the values of CO 2 production.…”
Section: Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They suggested that the main factors explaining this variation are the annual mileage, the regularity of daily driving, and the likelihood of long-distance trips. As Badin et al recently reported, higher emission factor would be expected if U.S. UFs are used in our study. As reported in WLTP regulation, once a significant number of PHEVs will be on the market, UF factors will have to be modified to be able to better capture their real usage and coherently assign the correct weighting to the values of CO 2 production.…”
Section: Results and Discussionsupporting
confidence: 88%
“…CO 2 emissions from the PHEV were 3 times higher than those reported for a power split plug-in hybrid (AER ∼83 km) and 2 times higher than those for a series plug-in hybrid, both tested under similar conditions (23 °C using WLTP). The BEVx’s CO 2 emissions were half of those reported by Badin et al These results indicate that a wide variety of OVC-HEVs is available and their electric range will be associated with the CO 2 that they will emit.…”
Section: Results and Discussionmentioning
confidence: 62%
“…As reported in [16], energy estimation models are generally created for the purpose of EV drivetrain design and optimization [17,18], assessment of the influences on the energy consumption [10,19,20], global energy consumption or grid impact due to the introduction of EVs or hybrid vehicles [14,15], or (all-electric) range prediction [21]. Energy estimation for the purpose of range prediction either relies on vehicle simulations where drivetrains and vehicle behavior are being simulated [13,22], sometimes down to the component level, or statistical models.…”
Section: Introduction and State-of-the-artmentioning
confidence: 99%
“…The fuel and electricity consumption for the seven passenger cars and the three buses were estimated using IFPEN vehicle simulators based on the Simcenter Amesim™ software. These conventional, hybrid, and EV simulators were developed and validated through component and vehicle tests (Badin et al 2015, Badin et al 2013, Da Costa et al 2012, Marc et al 2010). The objective is to assess the energy carrier consumption in both the WLTP homologated driving cycle and the Artemis urban cycle (André 2004) for passenger cars and in an urban Paris-type driving cycle for buses.…”
Section: Goal Scope and Products Systemsmentioning
confidence: 99%
“…The TTW stage corresponds to the use phase, where the energy carrier is consumed to propel the vehicle. An inhouse vehicle simulator based on Simcenter Amesim TM software(Badin et al 2015, Badin et al 2013) is used to assess the vehicle's fuel and electricity consumption, during both the WLTP and urban driving cycles, and for passenger cars and buses. Pollutant emissions are recorded according to the Euro6b norms for CO, NOx, PM, and hydrocarbon compounds (HC) for gasoline.…”
mentioning
confidence: 99%